SUBAKASTAWA DALAM PERSPEKTIF RAGAM GARAP PENYAJIANNYA - Sigit Setiawan (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2020)
Subakastawa dalam Perspektif Ragam Garap Penyajiannya This study intends to describe the variety of Subakastawa's musical works. The method used is descriptive-analytic using Kuntowijoyo's developmental approach and Rahayu Supanggah's approach to work. The development of Kuntowijoyo helps to see the variety and interpretation of musical works from one period to another which is identical to the usefulness of the music itself, while the working approach is used as a tool to dissect the musical situation in the intended musical. The result of this research is that there are five types of work on Subakastawa, namely; Working on the public, Subakastawa Cara Balen, Subakastawa Winangun, Subakastawa Rinengga and Subakastawa in the context of shadow puppet shows.